Influence of post hatch Saccharomyces cerevisiae supplementation on performance, slaughter traits and serum biochemistry of broiler chicken - RAI, KOMAL PRASAD; GENDLEY, M K; TIWARI, S P; SAHU, TARINI; NAIK, SURENDRA KUMAR (The Indian Journal of Animal Sciences, 2015)
Day-old Vencobb broiler chicks (180) were randomly allocated to 2 treatment groups with 9 replicates of 10 chicks in each to study the effect of post hatch Saccharomyces cerevisiae supplementation on growth performance, slaughter traits and biochemical profile. The trial lasted for 5 weeks. Two types of diet were formulated for first week which contained 0% and 0.5% S.cerevisiae respectively. After first week post-hatch period chicks were fed ad lib. with the normal basal diet as per Bureau of Indian Standard (BIS 1992) recommendations till completion of experiment. Maximum conversion of feed into gain was recorded in S. cerevisiae supplemented birds. The chicks attained relatively higher dressing percentage in the same group. Birds fed yeast had more protein in breast and thigh muscle whereas serum HI titre was nonsignificant among treatments. Maximum triglyceride was recorded in control group while other biochemical constituents did not differ significantly among treatments. It may be concluded that post hatch S. cerevisiae supplementation in the diet improves the overall FCR, dressing percentage and reduces triglyceride level in broiler chicken.